Associated factors in the development of rapidly progressive interstitial lung disease in patients with idiopathic inflammatory myopathies: a systematic review and meta-analysis - Yuan, Weiwei; Zhou, Xuefei; Yang, Yahui; Zhang, Shijie; He, Xing; Ji, Jiaqi (Frontiers in Immunology, 2025)
ObjectivesInterstitial lung disease (ILD), the main pulmonary manifestation of idiopathic inflammatory myopathy (IIM), frequently develops into rapidly progressive ILD (RP-ILD) with significantly worse prognosis. This meta-analysis identified risk and protective factors associated with developing RP-ILD in IIM patients.MethodsPubMed, Embase, Web of Science, and Scopus (up to October 2024) were searched, analyzing 21 retrospective studies (2,099 patients). Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were collected. Subgroup analysis was performed based on the RP-ILD definition. Sensitivity analysis and publication bias assessments (Egger’s test and trim-and-fill method) were performed.ResultsThe associated risk factors for RP-ILD development in IIM patients included age (OR = 1.014, 95% CI: 1.002–1.025), clinically amyopathic dermatomyositis (OR = 3.023, 95% CI: 1.491–6.130), mechanic’s hands (OR = 1.421, 95% CI: 1.054–1.915), fever (OR = 3.090, 95% CI: 1.933–4.939), pulmonary infection (OR = 2.610, 95% CI: 1.457–4.677), anti-melanoma differentiation-associated gene 5 (anti-MDA5) antibodies (OR = 6.044, 95% CI: 4.331–8.435), anti-Ro-52 antibodies (OR = 2.425, 95% CI: 1.807–3.255), and elevated levels of ferritin (OR = 5.844, 95% CI: 4.121–8.287), lactate dehydrogenase (OR = 3.627, 95% CI: 2.406–5.466), erythrocyte sedimentation rate (OR = 1.598, 95% CI: 1.089–2.344), aspartate aminotransferase (OR = 2.666, 95% CI: 1.864–3.814), alanine transaminase (OR = 2.702, 95% CI: 1.737–4.201), and C-reactive protein (OR = 3.366, 95% CI: 2.149–5.274), whereas longer disease duration (OR = 0.790, 95% CI: 0.638–0.977) and dysphagia (OR = 0.773, 95% CI: 0.653–0.916) were potential protective factors.ConclusionThis meta-analysis of 21 retrospective studies identified potential risk and protective factors associated with RP-ILD development in IIM patients, providing a basis for early identification and management.Systematic Review Registrationhttps://inplasy.com/inplasy-2025-4-0059/, identifier INPLASY202540059.